Wittgenstein jako filozof kultury - Dehnel, Piotr (Przestrzenie Teorii, 2020)
The paper raises the question of the extent to which Wittgenstein’s philosophy can be read as a philosophy of culture. The answer aims at grasping the conceptual bonds between three aspects of Wittgenstein’s thought: first, his taking both language and thinking to be expressions of a ‘form of life’ (or culture); second, his taking philosophical theories to result from some disorders that occur in ‘language games’; and third, his critique and rejection of the scientific and technical civilization. The paper advances the thesis that the task of bringing words back from their metaphysical to their everyday use – recommended by Wittgenstein – can be understood as a critique of scientism and culture dominated by scientific and technical rationality.